Measuring Health-Related Quality Of Life Among Patients With Chronic Heart Failure And The Costeffectiveness And Affordability Of Empagliflozin For Heart Failure Treatment: The Malaysian Perspective - Tan, Yi Jing (2024)
Heart failure (hf) causes debilitating symptoms, reduced functional capacity, and an increased risk of hospitalisation and mortality, placing a significant strain on the malaysian ministry of health (moh), and adversely impacting patients’ healthrelated quality of life (hrqol). Despite its prognostic value, hrqol among local hf patients remains unexplored. Hf is often categorised using a left ventricular ejection fraction (lvef) cut-off of 40% to distinguish between the lvef≤40% and lvef>40% subgroups, which differ in pathophysiology, comorbidities, and responses to available treatments. Although trials have demonstrated empagliflozin’s efficacy and safety in both hf subgroups, evaluating its cost-effectiveness and affordability is crucial for decision-making about its adoption within the moh. While local economic analyses suggest empagliflozin’s cost-effectiveness and affordability for treating the lvef≤40% subgroup, these factors remain to be confirmed for the lvef>40% subgroup. Moreover, previous cost-effectiveness analysis (cea) did not incorporate local utility data, limiting the generalisability of the findings to the local context. This research aimed to address gaps in local hrqol and utility data for hf, and to perform a cea and budget impact analysis (bia) of empagliflozin treatment across the full lvef spectrum.